2010
DOI: 10.1155/2010/391586
|View full text |Cite
|
Sign up to set email alerts
|

Structural fluctuation of proteins revealed by terahertz time-domain spectroscopy

Abstract: Abstract.We have measured spectra of the absorption coefficient and refractive index of hen egg white lysozyme in the wavenumber region from 7 cm −1 to 50 cm −1 by terahertz (THz) time-domain spectroscopy. From comparison with the results of the inelastic neutron scattering experiment it is concluded that analysis of the THz spectra provides information on the vibrational density of states. We studied temperature dependence of the THz spectra as well as hydration effect on them to discuss structural fluctuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…16 A well-defined dynamical transition related to biomolecule functioning above specific hydration levels (27% w/w), or temperatures (above 200 K), is detectable in THz spectrum. [16][17][18][19][20] Another study reveals the existence of structural collective modes for cytochrome c protein. 15 Solvated proteins (lysozyme and bovine serum albumin (BSA)), along with alcohols, have been also studied at different concentrations by micro-fluidic systems 4,21 over 50-110 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…16 A well-defined dynamical transition related to biomolecule functioning above specific hydration levels (27% w/w), or temperatures (above 200 K), is detectable in THz spectrum. [16][17][18][19][20] Another study reveals the existence of structural collective modes for cytochrome c protein. 15 Solvated proteins (lysozyme and bovine serum albumin (BSA)), along with alcohols, have been also studied at different concentrations by micro-fluidic systems 4,21 over 50-110 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Water plays a key role in structural organization of biomolecules and is a driving force that stimulates proteins to obtain their folded, functional state . Over the past decade, studies of water solutions of different molecules in the tetrahertz (THz) and sub-THz domain have attracted growing interest by many. They are stimulated by the fact that any molecule dissolved in water alters the dynamics of the surrounding water molecules to adopt quasi-coherent or organized character. This happens primarily via a reorganized, loose hydrogen-bond network.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies on the dynamical transition of proteins such as lysozyme and bacteriorhodopsin by THz spectroscopy have shown that the present experimental results are quite similar to those obtained by EINS where the motions of atoms constituting the protein are monitored. 21,39 Therefore, we conclude that the major contribution is from the atomic motions of the polypeptide itself. We will further discuss the microscopic origin of the dynamical transition of polyE in Section 5.3.…”
Section: Microscopic Origin Of the Dynamical Transitionmentioning
confidence: 72%